Intellectual property rights, development, and catch-up an international comparative study - Odagiri, Hiroyuki, 1946- (Oxford : Oxford University Press, 2010)
For most countries, economic development involves 'catching up' with leading countries. This needs more than physical assets & labour: it requires technological capabilities, educational attainment, entrepreneurship, & development of the necessary institutional infrastructure, including intellectual property rights, particularly patents.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intellectual property -- Economic aspects -- Developing countries; Economic development -- Developing countries